2008
DOI: 10.1111/j.1439-0272.2008.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm ultrastructure and meiotic segregation in a group of patients with chronic hepatitis B and C

Abstract: Little is known about the effect of chronic hepatitis B and hepatitis C on sperm quality. In this study, we analysed sperm quality from selected patients with chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infections. Semen samples were examined by light and transmission electron microscopy (TEM). TEM data were elaborated with a mathematical formula able to indicate a fertility index and the presence of the three main sperm pathologies: apoptosis, immaturity and necrosis. Meiotic chromosome segrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 21 publications
(19 reference statements)
1
41
2
1
Order By: Relevance
“…This is consistent with the observations by Zhao et al (13), who reported comparable PRs and implantation rates of IVF and embryo transfer treatment between 102 infertile couples with the husbands (but not the wives) being HBV seropositive and another 204 couples seronegative for HBV. In addition, despite previous evidence of possible negative effects of HBV on sperms (4,5), both our study and that by Pirwany et al (7) did not demonstrate any significant differences in semen parameters or fertilization rate between the HBV and the control groups. Because HBV can be found in cervical and vaginal secretion (14), we would speculate that HBV infection may induce inflammatory changes in the female lower genital tract, and that IVF and embryo transfer treatment can overcome some of these inhibitory effects on sperm function and therefore, it was associated with a higher success rate.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…This is consistent with the observations by Zhao et al (13), who reported comparable PRs and implantation rates of IVF and embryo transfer treatment between 102 infertile couples with the husbands (but not the wives) being HBV seropositive and another 204 couples seronegative for HBV. In addition, despite previous evidence of possible negative effects of HBV on sperms (4,5), both our study and that by Pirwany et al (7) did not demonstrate any significant differences in semen parameters or fertilization rate between the HBV and the control groups. Because HBV can be found in cervical and vaginal secretion (14), we would speculate that HBV infection may induce inflammatory changes in the female lower genital tract, and that IVF and embryo transfer treatment can overcome some of these inhibitory effects on sperm function and therefore, it was associated with a higher success rate.…”
Section: Discussioncontrasting
confidence: 83%
“…It has also been shown that HBV infection can increase the instability of sperm chromosomes (4). Although the semen parameters are not necessarily compromised, the sperm apoptosis and necrosis may be within normal range (5), which can be a problem in natural fertility as well as in ART. Similarly, HBV antigen and DNA can also be detected in the ovum or ovarian tissue (6), but its implications other than vertical transmission remain unclear.…”
mentioning
confidence: 98%
“…Durazzo et al (5) reported that the sperm concentration between controls and HCV patients was different, suggesting a possible negative influence of HCV on spermatogenesis. Moretti et al (4) added that sperm concentration was reduced in 5 (38.5%) out of 13 of their HCV patients in their study; Hofer et al (9) and Lorusso et al (6) also reported low sperm concentration in most or all of their chronic HCV patients compared with fertile controls. Safarinejad et al (10) also showed that in HCV patients the mean total sperm count, motility, and normal morphology were significantly lower than in controls.…”
mentioning
confidence: 87%
“…Most studies concerned with the reproductive aspect of HCVinfected men have focused on the risk of viral transmission and the presence or absence of viral genome in semen and/or spermatozoa, especially the studies of couples considering assisted reproductive technologies (4). It has been suggested that chronic HCV infection can alter seminal parameters and reproductive hormone profiles as part of its extrahepatic manifestation, with a possible negative effect on spermatogenesis and/or semen parameters (5).…”
mentioning
confidence: 99%
“…Eine Lagerung in Gasphase kann das Transmissionsrisiko weiter reduzieren. In diesem Zusammenhang soll darauf hingewiesen werden, dass sich auch bei HIV-Patienten mit [20] oder ohne [4] Aids und bei Hepatitis-Bund -C-Infektionen [7,16] gewisse Hinweise auf eine reduzierte Spermaqualität zeigten, die aber wenig ausgeprägt waren. …”
Section: E Vor Spermakryokonservierungen Ist Der Ausschluss Von Hiv-uunclassified